Implementation of the Use of Trademark Rights in the Development of UMKM in Medan City - Atika Sunarto; Keren Trifena Ompusunggu; Muhammad Ali Adnan (Journal of Law, Politic and Humanities, 2025)
A brand is a logo or symbol representing a company's identity. Brands are highly influential in attracting customers and differentiating products from competitors. A brand is considered intellectual property, allowing differentiation between similar products and services, thereby maintaining quality. Trademark laws emphasize the exclusive rights of the brand owner to use it personally or to grant permission to others. Small and Medium Sized (SMEs) play a crucial role in the Indonesian economy by creating jobs and increasing community income. This highlights the importance of branding for SMEs, especially in Medan, where SMEs significantly contribute to economic growth and development. Trademark registration for SMEs actors involves a trademark renewal process that adds to the burden due to additional costs and periodic administrative requirements. All of this makes SMEs actors reluctant to register trademarks, even though this step is crucial for protecting and strengthening their business in the market